In vitro Modeling of Embryonal Tumors - Custers, Lars; Paassen, Irene; Drost, Jarno (Frontiers in Cell and Developmental Biology, 2021)
A subset of pediatric tumors affects very young children and are thought to arise during fetal life. A common theme amongst these embryonal tumors is that they hijack developmental programs, causing a block in differentiation and, as a consequence, unrestricted proliferation. Embryonal tumors therefore typically maintain an embryonic gene signature not found in their differentiated progeny. Still, the processes underpinning malignant transformation remain largely unknown, which is hampering therapeutic innovation. To gain more insight into these processes, in vitro and in vivo research models are indispensable. However, embryonic development is an extremely dynamic process with continuously changing cellular identities, making it challenging to define cells of origin. This is crucial for the development of representative models, as targeting the wrong cell, or targeting a cell within an incorrect developmental time window can result in completely different phenotypes. Recent innovations in in vitro cell models may provide more versatile platforms to study embryonal tumors in a scalable manner. In this Review, we outline different in vitro models that can be explored to study embryonal tumorigenesis and for therapy development.